Comparison of 2-D calculations from periapical and occlusal radiographs versus 3-D calculations from CAT scans in determining bone support for cleft-adjacent teeth following early alveolar bone grafts - Rosenstein, S W; Long, Jr, R E; Dado, D V; Vinson, B; Alder, M E (The Cleft palate-craniofacial journal, 1997)
This investigation was conducted to determine the agreement between three-dimensional (3-D) calculations from CAT scans and two-dimensional (2-D) calculations from standard dental radiographs in evaluating bone support for cleft-adjacent teeth after primary bone grafting. This retrospective study utilized CAT scans and dental radiographs taken of the alveolar cleft in patients an average of 11 years after primary bone grafting. The subjects were patients treated by the Cleft Palate Team at Children's Memorial Hospital and Loyola University Medical Center, Chicago, Illinois. Fourteen UCLP patients (9 males, 5 females) agreed to participate in this study by undergoing CAT scan assessment of their alveolar cleft sites. They also had to have periapical or occlusal radiographs of the grafted cleft site taken within 6 months of the CAT scan. All patients underwent primary lip repair, placement of a passive palatal plate, primary alveolar bone grafting (mean age 6.4 months), and palatoplasty before 1 year of age. Major tooth movement through final orthodontics was completed by the time of the radiographic assessment. CAT scan sections were reformatted and reconstructed to three-dimensionally calculate the percentage of root covered by bone support for the 15 teeth adjacent to the graft cleft sites. Dental radiographs of the same teeth were also traced and digitized. Percentages of root supported by bone were also established using the dental radiographs by dividing the amount of root covered by bone, by the anatomic root length. A paired, two-sample t test revealed no significant differences between the two methods of assessment, while linear regression showed a statistically significant correlation between the CAT scan assessment and the percentages found on the radiographs. Routine dental radiographs were able to estimate the total 3-D bone support for the roots of cleft adjacent teeth as determined by CAT scan to a statistically significant degree when groups where compared. The clinical significance for evaluation of individual cases was less impressive with a wide range of variability and a level of agreement that required acceptance of differences up to 25%.